Hot tub time machine 2 - Pink, Steve; Corddry, Rob; Robinson, Craig, 1971-; Duke, Clark, 1985- (Hollywood, California : Paramount, 2017)
Follows the adventures of Lou, his best friend Nick, and his son Jacob as they hop into the time traveling hot tub once again, accidentally traveling to the year 2025 instead of the past.
Sequel to "Hot tub time machine" (2010).
Wide screen 1.85:1.
Rob Corddry, Craig Robinson, Clark Duke, Adam Scott, Gillian Jacobs.
MPAA rating: R.
Keywords: Time travel -- Drama; Hot tubs -- Drama; Male friendship -- Drama; Fiction films; Feature films; Comedy films; Science fiction films